Analysing the impact of budgetary controls on capital projects to the operational performance. - Munyenyiwa, Tafadzwa (Midlands State University, 2020)
This paper specifies the impact of budgetary control measures on capital projects to the operational performance of the Zimbabwean aviation industry. In this study, the major objective was to identify the impact of budgetary control measures on operational performance. Mixed research design was used in data collection incorporating both the qualitative and quantitative approaches so that they could accompaniment each other in investigating the impact of budgetary control on capital projects to the operational performance of the aviation industry. Primary data was collected through research instruments which were questionnaires and interview. The case study used was Civil Aviation Authority of Zimbabwe. The population samples were drawn from departments of Civil Aviation Authority of Zimbabwe and the judgemental sampling technique was used. Budgetary controls have a positive impact on the operational performance which was also reviewed by STATA 11 results that a single unit increase in budgetary controls has an impact of 88.12%. The researcher closed up the chapters by recommending that Civil Aviation Authority of Zimbabwe may develop more effective budgetary controls should be put in place and also employees should be equipped and trained on how effective budgetary controls can be achieved. The researcher also recommends that the organisation should consider contracting labour from within the borders of Zimbabwe. The organisation is recommended to make use of Airport Revenue Sustainable Tools (ARST) to lessen the burden on budgets and capital projects. The researcher recommends the issue of considering Public Private Partnerships and this is a suggestion for the further study.